Corrosion deterioration of steel in cracked SHCC - Paul, Suvash Chandra (2018)
The presence of cracks is unavoidable in reinforced concrete structures and also a gateway for chloride into concrete, leading to corrosion of steel reinforcing bars. So, crack control, crack width limitation and chloride threshold levels are well-established concepts in durability of reinforced concrete structures. This paper reports on accelerated chloride-induced corrosion in cracked reinforced strain-hardening cement-based composites and reinforced mortar beams, both in loaded and unloaded states. Corrosion rates are monitored and loss of mass and yield force, as well as corrosion pitting depth in steel bars are reported. The chloride content at different depths in specimens is also determined through XRF, and through chemical testing of acid and water soluble chloride content by titration. Finally, different relationships are drawn between crack properties, mass loss, yield force, corroded depth and chloride levels at the steel surface for different cover depths. It is found that the crack spacing and free chloride at the steel surface level are best correlated to the corrosion damage in the specimens.